Primary School Teachers’ Long-Term Strategies for Teaching English to Young Learners: A Narrative Inquiry - Meidy Kautsar Arriv; Asmida Yanti Siregar; Fadliyah Uzma (FOSTER: Journal of English Language Teaching, 2026)
This study aims to investigate the strategies used by primary school teachers in teaching English to young learners and the strategies that have been effective in teaching English to young learners from the past until now. This study employed a qualitative design using a narrative inquiry approach involving two experienced primary school teachers with more than 20 years of teaching experience to explore their long-term teaching practices. Data were collected through semi-structured interviews and were analyzed thematically. The findings demonstrate that both teachers view building close teacher-student relationships as a central strategy, as it supports students' comfort and readiness to learn. Based on long teaching experience, both teachers consistently used gradual instruction and practical classroom strategies such as Total Physical Response, songs, visual materials, and technology to support learning. Although some earlier strategies were no longer used because they were less effective, the core teaching practices remained stable despite ongoing curriculum changes. Overall, the teachers described their strategies through everyday classroom practices rather than theoretical terms.